PENGARUH PROGRAM PEMUTIHAN PAJAK KENDARAAN BERMOTOR, KESADARAN WAJIB PAJAK, SOSIALISASI PAJAK, DAN PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI PADA KANTOR BERSAMA SAMSAT SURABAYA SELATAN) - Tituk Diah Widajantie; Saiful Anwar (Behavioral Accounting Journal, 2020)
This research was conducted for knowing the influence of motor vehicle tax bleaching program, taxpayer awareness, tax socialization, and tax administration service toward taxpayer compliance to pay motor vehicle tax (Pajak Kendaraan Bermotor- PKB) at SAMSAT office of Surabaya Selatan. The total sample for this study was 100 respondents calculated using the sampling method namely simple random sampling. Collected data using a questionnaire distributed to respondents. Hypothesis testing in this research used multiple linear regression in SPSS 23. The analysis results show that motor vehicle tax bleaching program, taxpayer awareness, and tax administration service influence taxpayer compliance in paying PKB. Meanwhile, tax socialization does not have an effect on taxpayer compliance in completing the PKB.